CuTe chains on Cu(111) by deposition of one-third of a monolayer of Te: Atomic and electronic structure - Kißlinger, Tilman; Raabgrund, Andreas; Geldiyev, Begmuhammet; Ammon, Maximilian Michael; Rieger, Janek; Hauner, Jonas; Hammer, Lutz; Fauster, Thomas; Schneider, M. Alexander (Physical Review B, 2020)
The surface atomic and electronic structure after deposition of one-third of a monolayer Te on Cu(111) was determined using a combination of low-energy electron diffraction (LEED), scanning tunneling microscopy and spectroscopy (STM/STS), angle-resolved single and two-photon photoelectron spectroscopy (ARPES /AR-2PPE), and density functional theory (DFT) calculations. Contrary to the current state in literature, Te does not create a two-dimensional surface alloy but forms Cu2Te2 adsorbate chains in a (2√3×√3)R30∘ superstructure. We establish this by a high-precision LEED-IV structural analysis with Pendry R factor of R=0.099 and corroborating DFT and STM results. The electronic structure of the surface phase is dominated by an anisotropic downward dispersing state at the Fermi energy EF and a more isotropic upward dispersing unoccupied state at E−EF=+1.43eV . Both states coexist with bulk states of the projected band structure, and are therefore surface resonance